RÔLE DES JOURNALISTES DANS LES CONFLITS INTERCOMMUNAUTAIRES DANS LA VILLE DE KISANGANI. CAS DES COMMUNAUTÉS MBOLE ET LENGOLA DANS LA COMMUNE DE LUBUNGA - WONGO, Armand KITOKO; Ngaya, Lotika; Lioso, Franck Muzinga; Bedidjo, Théodore Ubemu (IJRDO - Journal of Social Science and Humanities Research, 2023)
This article is the result of an investigation carried out in Kisangani with a view to knowing the role that journalists from the capital of Tshopo have played in the conflicts between the communities. The city of Kisangani has been enriched for some time by several media and media professionals. The major concern of this article is to make, on the one hand, a contribution to improving the work of journalists in conflict resolution. Because, peace journalism, which is journalism to act, wants to be the opposite of a journalistic practice which reduces the facts of news, even the most sensitive, to a space of struggle of force between good and bad. Between winners and losers, which the media limit themselves to commenting on by counting the number of deaths. The peace process being aborted by each other, which they consider complete only when one of the parties has got the better of the other. Then, inform scientists about the crux of the conflict or crisis, with the aim of pushing them to continue this study and also to help media professionals in Kisangani to play their role well according to social responsibility by being on the ground to to know about what is happening in society in order to provide good information to the population in order to avoid leaving room for speculation in public opinion and this will enable those who have power over the res publica to control on a daily basis all the problems that may arise in my company, such as conflicts or crises. It is clear that the media generally prefer to focus on the spectacular aspects. They reduce conflicts to a zero-sum game, a confrontation between good and bad, without nuances. However, the work of the journalist during the war is oriented only in this way, because it is based only on the visible of the conflicts, reporting the atrocities committed by the enemy. The object of any media entity is to educate, denounce and restore confidence, to analyze the underlying causes of conflicts. Thus, the journalist must adapt in the action to humanize the protagonists so that each of the parties can better understand the other. Basically, it must allow the emergence of alternatives to violence. To achieve this objective, the media company must not only have sufficient financial resources but also qualified human resources to ensure its emergence. Especially since the efficiency in the company depends as much on the quality of organization and the management of conflicts and crisis as on that of the equipment and the processes of execution of the material tasks. Over the past few decades, the individual or even overall performance of public media companies and journalists in the development and peace effort has been negative, given the multiple difficulties that Congolese journalists face, in particular the mismanagement of conflicts by certain sectoral authorities, political interference, disinformation, lack of mastery of journalistic ethics and deontology which stifles them from working for complete independence. However, journalists struggle to thrive and live up to their social responsibility because of the realities of the environment in which they operate. This situation is at the root of the lack of transparency, independence, freedom of expression and freedom of the press. Indeed, some of them resort to unofficial sources in order to be up-to-date. This practice does not encourage the population to always be up to date with the news. A proactive journalist will therefore watch over the content broadcast and finally respond quickly to circumstances and possible abuses. As a result, the media are a powerful social force, both as sources of information and as a tool for opinion education.